E-Module for Learning Volley Ball Using Character Based on Adobe Flash Cs6 - Prasetyo, Dian Estu; Handayani, Fitry (Journal of Education Technology, 2020)
The low character of students plus the absence of learning resources that support learning about basic volleyball technical skills in the Covid-19 pandemic situation makes it difficult for lecturers to teach. The purpose of this research and development was to produce a character-based volleyball e-module for students using Adobe CS 6 with valid, practical, and effective criteria. This research is a development research. This research used the ADDIE model which consists of 5 stages, namely, needs analysis (analysis), design (design), develop (develop), implement (implement), evaluate (evaluate). The research data was using quantitative data that the data were taken from the results of the evaluation by the validator and the practical data was taken from the responses of lecturers and students to the e-module. The research instruments were validation questionnaires, practicality questionnaires, student character effectiveness sheets, volleyball skills assessment effectiveness sheets. The results of the e-module research on character-based volleyball learning for students using Adobe Flash CS-6 have met the criteria of being valid, practical and effective. From these results, the e-module volleyball learning based on character education for students using adobe flash CS 6 is effective for learning, especially in volleyball lectures, namely the basic technique of volleyball.